Representation of Social Inequality in the Film Shoplifters: A Semiotic Study of Roland Barthes - Danuta Korpas, Azalea; Zamroni , Muhammad; Sukmawati, Ni Luh Ayu; Kartika, Bambang Aris; Hartanto, Denny Antyo (Cultural Narratives, 2025)
This study examines the representation of social inequality in the film Shoplifters (2018) by Hirokazu Kore-eda through the lens of Roland Barthes semiotic theory. As an audiovisual medium, film reflects social realities and conveys ideological messages, with Shoplifters serving as a poignant depiction of poverty and marginalization. The study explores how mise-en-scene elements such as setting, costume, make up, and camera angles communicate deeper meanings through Barthes three levels of signification: denotation, connotation, and myth. Using a descriptive qualitative method and focusing on two key scenes, the research identifies how the film presents various dimensions of social inequality including economic hardship and social exclusion. The findings reveal that the Shibata family's unconventional structure and survival strategies underscore systemic disparities and challenge dominant societal norms.